Accidental Detection of Cocaine in Urine in Pediatric Patients: Case Series and Literature Review - Martina Focardi; Ilenia Bianchi; Marta Romanelli; Valentina Gori; Laura Nanni; Fabio Vaiano; Stefania Losi (Children)
Infantile occult exposure to cocaine in domestic environments represents a complex clinical and medico-legal problem, which can be associated with abuse and neglect and with potential short- and long-term health risks for children. The authors present a retrospective study on 764 children under 14 years old who accessed the Emergency Department of IRCCS Meyer from 2016 to 2023 and were included in the GAIA (Child and Adolescent Abuse Group) protocol for suspected maltreatment and abuse, and for which a urine toxicology analysis was performed. The aim is to discuss the medico-legal implications and highlight the need for a thorough evaluation and management of such situations. Urine screening tests for substances of abuse (e.g., cocaine, opiates, etc.) were performed with an EMIT® Siemens VIVA-E drug testing system (Siemens, Newark DE) in 124 cases for which the child’s clinical condition raised suspicion of intoxication, or the family context indicated distress or substance abuse dependency. The screening results revealed the presence of cocaine and its main metabolite, benzoylecgonine, in the urine of 11 children. In one case, a single girl was brought to the Emergency Department by staff from the facility where she and her mother were staying. In most of the cases, children were brought to the Emergency Department by their parents who accessed the Emergency Department due to various clinical manifestations (drowsiness, agitation, seizures, hypotonia, diarrhea, vomiting, etc.), except for one case of eye trauma suspected to be caused by abuse or neglect by one of the parents. Three of the children did not have signs or symptoms attributable to substance exposure, whilst eight of the cases presented some of the symptoms associated with occult infant exposure to cocaine, such as neurological manifestations, seizures, gastrointestinal symptoms, and respiratory depression. The probable mode of intake was mostly through breastfeeding and continuous environmental exposure due to domestic contamination or inhalation of “crack”. In the case of a 12-hour-old infant, there was probable prenatal in utero exposure. All the children were hospitalized, some for medical reasons and others solely as a precautionary measure for proper care. In all cases, a report was made to the Prosecutors as required by the Italian Penal Code, as well as to the Court of Minor. The study highlighted the importance of a multidisciplinary approach involving pediatricians, social workers, and forensics, as well as close collaboration with the relevant authorities, as the Gaia service at IRCCS Meyer offers. The occasional detection of cocaine in cases that showed no suspicion of intoxication led to a modification of the procedure and the development of a standardized protocol at IRCCS Meyer both in terms of prevention and in the detection and interception of hidden cases, in order to intervene early and initiate the necessary care pathways (secondary prevention). This protocol includes routine toxicological urine testing in all suspected or confirmed cases of child abuse, not just in those where symptoms might suggest a suspicion of intoxication.